The Relationship of Chollinesterase Levels to Cognitive Status In Village Farmers Pakis, Jember District - I Made Putra Wira Negara; Kristianningrum Dian S; Alif Mardijana (Green Publisher Indonesia, 2024)
This study aims to analyze the relationship between cholinesterase levels and cognitive status in farmers in Village, Panti District, Jember Regency. High use of pesticides in the agricultural sector can increase the risk of poisoning, which has an impact on health, especially the nervous system and cognitive function. The research method used was observational with a cross-sectional design, involving 30 farmers who used organophosphate and carbamate pesticides. Cognitive status was measured using the Mini Mental State Examination (MMSE). The results showed that there was a decrease in cholinesterase levels in some farmers, but the analysis with the Spearman correlation test showed no significant relationship between cholinesterase levels and cognitive status (p > 0.05). This research is expected to provide information about the impact of pesticides and the importance of using personal protective equipment for farmers